Genetic Variability of Aspergillus flavus Isolates from a Mississippi Corn Field - Cesar D. Solorzano; Hamed K. Abbas; Robert M. Zablotowicz; Perng-Kuang Chang; Walker A. Jones (The Scientific World Journal)
A nontoxigenic Aspergillus flavus strain, K49, is currently being tested as a biological control agent in corn fields in the Mississippi Delta. However, little is known about the overall genetic diversity of A. flavus from year to year in corn fields and specifically in Mississippi. Our objective was to assess the genetic variability of A. flavus isolates from different seasons, inoculum sources, and years, from a no-till corn field. Of the 175 A. flavus isolates examined, 74 and 97 had the typical norB-cypA type I (1.5 kb) and type II (1.0 kb) deletion patterns, respectively. Variability in the sequence of the omtA gene of the majority of the field isolates (n=118) was compared to strain K49. High levels of haplotypic diversity (24 omtA haplotypes; Hd = 0.61 ± 0.04) were found. Among the 24 haplotypes, two were predominant, H1 (n=71), which consists of mostly toxigenic isolates, and H49 (n=18), which consists of mostly atoxigenic isolates including K49. Toxigenic isolates were prevalent (60%) in this natural population. Nonetheless, about 15% of the population likely shared the same ancestral origin with K49. This study provides valuable information on the diversity of A. flavus. This knowledge can be further used to develop additional biological control strains.